Exploring EFL Teachers’ Teaching Process in Reading PISA-Like Reading Texts - Karima Putri Rahmadina; Emi Emilia (Ranah: Jurnal Kajian Bahasa, 2022)
This paper presents partial results of a research project aiming to develop a training program for teachers to teach PISA-like reading texts with 24 participating teachers (10 Indonesian language teachers and 14 English language teachers) conducted in 2021. The result of the study has also been reported in Emilia, Sujatna, and Kurniasih (2022).  This study centers around the early stage of training, focusing on the teachers’ initial ability in teaching reading practice prior to the training. The data were collected from peer teaching and lesson plans made by the teachers prior to the sessions on teaching PISA-like reading texts. The data were then analyzed based on the theory of PISA Reading (OECD, 2019), reading as a social process (Wallace, 1992; Gibbons, 2014), and teaching reading through the use of text-based instructions (Emilia, 2011; Rose & Martin, 2012; Rose, 2020). The result of the study shows that some teachers had bridged the students’ access to text by activating their prior knowledge to help them understand the text. Nevertheless, some teachers had not provided guidance for the students when they read. This result suggests that the teachers still need guidance to teach reading, especially in teaching PISA-like reading texts. Hence, the data confirm the need for training teachers to teach PISA-like reading texts. AbstrakJurnal ini menyajikan sebagian hasil dari proyek penelitian yang bertujuan untuk mengembangkan program pelatihan bagi guru untuk mengajar teks membaca setara PISA dengan 24 guru peserta (10 guru bahasa Indonesia dan 14 guru bahasa Inggris) yang dilakukan pada tahun 2021. Bagian lain dari proyek penelitian ini juga telah telah dilaporkan dalam Emilia, Sujatna, dan Kurniasih (2022). Studi ini berpusat pada tahap awal pelatihan, yang berfokus pada kemampuan awal guru dalam mengajarkan membaca sebelum diberikan input pelatihan. Data penelitian diperoleh dari sesi peer teaching dan RPP yang dibuat oleh guru sebelum diberikan sesi input pengajaran teks bacaan mirip PISA. Data penelitian kemudian dianalisis berdasarkan teori PISA Reading (OECD, 2019), membaca sebagai proses sosial (Wallace, 1992; Gibbons, 2014), dan pengajaran bahasa berbasis teks (Emilia, 2011; Rose & Martin, 2012; Mawar, 2020). Hasil penelitian menunjukkan bahwa beberapa guru terlihat mampu untuk menjembatani akses siswa untuk membaca teks dengan mengaktifkan pengetahuan awal mereka yang dapat membantu mereka memahami teks. Namun demikian, beberapa guru terlihat masih belum memberikan bimbingan kepada siswa ketika mereka membaca. Hasil ini menunjukkan bahwa guru masih membutuhkan bimbingan untuk mengajar membaca, terutama dalam mengajar teks bacaan mirip PISA. Oleh karena itu, data mengkonfirmasi perlunya pelatihan guru untuk mengajar teks bacaan seperti PISA.